Superação da dormência em sementes de Brachiaria humidicola cv. BRS Tupi durante o armazenamento - Moreira, Daiani Ajala Luccas [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The Brachiaria humidicola cv. BRS Tupi is the first cultivar of B. humidicola indicated for use in Brazil and comes up as one more option for the humid areas of low and average fertility. As the majority of the tropical forage grass, freshly harvested se eds of this cultivar are affected by the phenomenon of dormancy. Despite the obvious importance of dormancy in freshly harvested seeds of Brachiaria , the mechanisms that are involved in overcoming dormancy that occurs during storage are still poorly unders tood. Thus, the present study was carried out with the aim to evaluate the overcoming dormancy in seeds of B. humidicola cv. BRS Tupi during different storage periods (0, 3, 6, 9, and 12 months). Seeds of B. humidicola cv. BRS Tupi were multiplied in the f ield, and after the drying process in the natural environment and processing, were stored. After the storage periods the seeds were evaluated according to its physiological changes through imbibition curves, evaluation of the water content of the seed part s (embryo and endosperm) during imbibition, germination of whole seeds , germination in different concentrations of gibberellic acid of whole seeds and naked caryopses, potential of growth of the embryo of naked caryopses in water restriction and germination of scarified seeds. The storage favors the increase of the water conten t of the parts of the seed during the imbibitions. The overcoming of dormancy happens with the removal of the seed coat showing possible mechanical barrier which is overcome during the storage due to the raise in the potential of growth of the embryo, possibly related to the action of GA on the seeds. The chemical scarific ation was not efficient in overcoming the dormancy during the storage

A Brachiaria humidicola cv. BRS Tupi é a primeira cultivar de B. humidicola indicada para uso no Brasil e surge como mais uma opção para áreas úmidas de baixa e média fertilidades. C omo a maioria das gramíneas forrageiras tropicais, sementes recém - colhidas dessa cultivar são afetadas pelo fenômeno da dormência . Apesar da evidente importância da dormência em sementes recém - colhidas de Brachiaria , os mecanismos que estão envolvidos na superação da dormência que ocorre durante o armazenamento ainda são pouco elucidados. Assim, este estudo foi conduzido com o objetivo de avaliar a superação da dormência em sementes de B. humidicola cv. BRS Tupi durante diferentes períodos de armazenament o (0, 3, 6, 9, e 12 meses). Sementes de B. humidicola cv. BRS Tupi foram multiplicadas em campo e, após o processo de secagem em ambiente natural e beneficiamento , foram armazenadas. Após os períodos de armazenamento , as sementes foram avaliadas quanto as suas alterações fisiológicas através de curvas de embebição, do teor de água das partes da semente (embrião e endosperma) durante a embebição, germinação de sementes inteiras , germinação de sementes inteiras e cariops es nuas em diferentes concentrações de ácido giberélico, potencial de crescimento do embrião de cariopses nuas em restrição hídric a e germinação de sementes escarificadas. O armazenamento favorece o aumento do teor de água das partes da semente durante a e mbebição. A superação da dormência ocorre com a retirada das coberturas da semente indicando possíveis impedimentos mecânicos que são superados durante o armazenamento devido ao aumento no potencial de crescimento do embrião, provavelmente relacionado à aç ão de GA nas sementes . A escarificação química não foi eficiente na superação da dormência durante o armazenamento
Keywords: Plantas forrageiras; Capim-braquiaria - Dormencia; Sementes - Germinação; Dormancy